Implementation Of Span Lapor Policy In Papua Pegunungan Province - Giban, Elai; Sartika, Ika (Riviera Publishing, 2025)
This study discusses the implementation of the policy of the National Public Service Complaint Management System – People's Online Aspiration and Complaint Service (SP4N-LAPOR) in Highland Papua Province with a qualitative method based on literature study. Nationally, SP4N-LAPOR is a one-stop integrated mechanism in handling public service complaints formed in accordance with the mandate of Law Number 25 of 2009 concerning Public Services and Presidential Regulation Number 76 of 2013. This system implements the principle of no wrong door policy, which ensures that every public report, regardless of origin or type, can be effectively channeled to the authorized agencies. The results of the study show that in Mountainous Papua, the implementation of SP4N-LAPOR is faced with a number of significant obstacles, both in terms of administrative, geographical, socio-cultural, and technological infrastructure. These challenges include the lack of complaint management teams in most districts, limited access to transportation and internet networks in mountainous areas, low intensity of socialization and digital literacy of the community, and lack of availability of ICT infrastructure. This condition makes the use of SP4N-LAPOR in the area still very low. The conclusions and suggestions submitted emphasize the importance of increasing the commitment and capacity of local governments, developing internet infrastructure, adjusting socialization strategies to socio-cultural contexts, and providing budgets according to the provisions, so that SP4N-LAPOR can be optimized as a public service complaint channel in the region.